Study on the impact behaviour of a new safety toe cap model made of ultra-high-strength steels - Costa, Sérgio Luís Ferreira (2016)
In this study the crashworthy performance of an ultimate safety toe cap model made of high-strength steel was evaluated. The structural response to impact loading conditions under normative requirements was properly related to the potential of light weight design for a significant thickness reduction. Two grades of fully martensitic steels were selected and numerical models modelling extensive plastic deformation and strain-rate dependence were performed. The mathematical description of the impact behaviour with the correlation of crashworthy properties was analysed and compared by applying two fundamental constitutive models: The Cowper-Symonds and Johnson-Cook constitutive equations. Experimental results of tensile testing at different strain rates and different directions of the sheet material were used to determine fundamental constitutive parameters for both steel alloys. The numerical simulation developed using an explicit dynamics software (ANSYS) was extensively compared to an experimental standard testing program of final prototypes. A local stiffening toe cap model with high energy absorption efficiency was also validated.